2022
DOI: 10.1183/16000617.0269-2021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac consequences of intermittent hypoxia: a matter of dose? A systematic review and meta-analysis in rodents

Abstract: AimIntermittent hypoxia (IH) is considered to be a major contributor to obstructive sleep apnoea-related cardiovascular consequences. The present meta-analysis aimed to assess the effects of IH on cardiac remodelling, function and infarct size after myocardial ischaemia across different rodent species and IH severities.Methods and resultsRelevant articles from PubMed, Embase and Web of Science were screened. We performed a random effect meta-analysis to assess the effect of IH on myocardium in rodents by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…These studies demonstrate different oxidative stress responses to IH among vascular beds that depend on the duration of total IH exposure as well as characteristics (number of cycles per hour, depth) of IH [ 56 ]. In recent meta-analyses performed on rodents, we demonstrated that the duration (acute exposure of few hours vs. chronic exposure of several days) and the depth of hypoxia (10% vs. 5%) impact the response to ischemia-reperfusion [ 57 ]. Since IH did not impact superoxide anion content or pro/anti-oxidant balance in the aorta, we cannot say that vascular oxidative stress is the main driver of an increase in BP under IH.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate different oxidative stress responses to IH among vascular beds that depend on the duration of total IH exposure as well as characteristics (number of cycles per hour, depth) of IH [ 56 ]. In recent meta-analyses performed on rodents, we demonstrated that the duration (acute exposure of few hours vs. chronic exposure of several days) and the depth of hypoxia (10% vs. 5%) impact the response to ischemia-reperfusion [ 57 ]. Since IH did not impact superoxide anion content or pro/anti-oxidant balance in the aorta, we cannot say that vascular oxidative stress is the main driver of an increase in BP under IH.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, chronic HIF-1 activation is recognized to induce deleterious effects. Indeed, sustained HIF-1α overexpression leads to cardiac hypertrophy [ 19 ], and we demonstrated that chronic IH is a potent inducer of its adverse effects on infarct size [ 20 , 21 ]. In line, we and others demonstrated an important cooperation between HIF-1 and ER stress in these detrimental effects.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of periodic breathing and exposure to mild intermittent hypoxia in neonates is not well established [ 1 , 32 ]. In animal models, mild intermittent hypoxia has shown both negative and positive effects on neurodevelopment and cardiovascular function [ 32 , 33 ]. However, in general, intermittent hypoxia is considered detrimental for neurodevelopment [ 1 , 34 ].…”
Section: Discussionmentioning
confidence: 99%